FORMULASI TABLET HISAP EKSTRAK GAMBIR (Uncaria gambir (Hunter) Roxb.) DENGAN VARIASI BAHAN PENGIKAT GOM ARAB (Gummi Acaciae) - Lutfi Chabib; Asih Triastuti; Rischi Dwi Irianti (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Gambier is one of the medicinal plants commonly used for chewing, which has benefits for oral health and dental. Gambier has a property as a remedy lozenges, stomachache, toothache, and can be used to prevent the formation of dental plaque. This research aims to create a dosage of dried extract in the form of lozenges. In these lozenges we used variations gummi acaciae to obtain a binder concentration that can produce tablets that meet the requirements. Gambier extract was obtained by remaceration, with 80% ethanol. Tablets formulated with a binder concentration gom arabic 10%, 17.5% and 25% using direct compression method. The results showed that the concentration variation can minimize the variation of the gummi acaciae weight uniformity, increased hardness, lower % fragility, and increase the time dissolved lozenges. All of tablets have good physical tablets properties. The third formula is the most acceptable by the respondents in terms of color, taste, and time of dissolution.